Correspondence between resident‐ and staff‐report on the QABF: Do justice‐involved youth agree with residential staff?. (22nd December 2022) - Sheridan, Daniel J.; Edgemon, Anna Kate; Rapp, John T.
Abstract: Residents in juvenile residential treatment facilities (JRTFs) often display various emotional, behavioral, and educational needs. Researchers have recently developed behavioral interventions to increase residents' appropriate behavior such as cooperation with facility staff instructions, accepting feedback from facility staff, and tolerating unpleasant events. However, there is not a generally accepted tool for assessing the operant function of residents' problem behavior in JRTFs. For various logistical reasons, indirect functional assessments may be more appropriate in a JRTF than manipulating either antecedent or consequent events. This study obtained scores on the Questions About Behavior Function (QABF) assessment for 17 residents from two dormitory staff members for each resident. To increase the number of respondents, each resident completed a QABF for their own behavior. Results revealed moderate to high correspondence (i.e., agreement) for highest and lowest potential operant function of problem behavior between combinations of JRTF staff and residents. These preliminary findings suggest additional research with the QABF in JRTFs is warranted.